Constant Torque Control of Induction Motor Using Variable Frequency Drive Based on Internet of Things - Syarah, Ullya; Yuhendri, Muldi (Journal of Industrial Automation and Electrical Engineering, 2024)
Many industrial devices operate using movements operated by electric motors. One type of motor that is widely used in industry is the three-phase induction motor. In order for the motor to operate according to needs, the motor needs to be controlled, such as controlling the rotation speed, controlling the direction of rotation, braking and starting current. Induction motor control in today's industry often uses power converters packaged in the form of Variable Speed Drive (VSD) modules. The use of this VSD allows control of induction motors with various methods, such as the scalar method (constant Volt/Hertz) or the vector control method. The VSD module also allows remote control and monitoring of the motor using the internet, so that the reliability of motor control can be improved. This study proposes control and monitoring of induction motors using the Omron 3G3JX-A VSD based on the Internet of Things (IoT). The motor is controlled using the scalar method in a constant torque configuration, so that the motor can operate more efficiently. The control and monitoring system is designed using PLC Omron CP2E-N, VSD Omron 3G3JX-A with CX-Programmer software, Node-red and Web server for remote access on smartphones. The design of the three-phase induction motor control and monitoring system based on IoT was tested and validated through laboratory experiments. The test results show that the proposed motor control and monitoring system has worked well according to the objectives. The motor can be controlled remotely using a smartphone and also from a PC